2010
DOI: 10.1136/ard.2009.116764
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ankylosing spondylitis on sick leave, presenteeism and unpaid productivity, and estimation of the societal cost

Abstract: Patients with AS not only have substantial sick leave but also experience restrictions while being at work and when performing unpaid tasks. Limitations in physical functioning are strongly associated with work restrictions. Societal costs of formal and informal care are comparable with the costs of sick leave and presenteeism combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
98
0
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 21 publications
12
98
0
8
Order By: Relevance
“…Musculoskeletal conditions are common among workingage adults (1,2); are a leading cause of disability (3), activity limitations (4), and work loss (5)(6)(7)(8)(9); and are associated with a significant burden and cost to the individuals living with these conditions and to society (10)(11)(12). It is critical to find ways to help individuals with musculoskeletal conditions to remain employed, especially as the potential burden of these conditions is expected to increase with the aging of the population in many industrialized nations (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal conditions are common among workingage adults (1,2); are a leading cause of disability (3), activity limitations (4), and work loss (5)(6)(7)(8)(9); and are associated with a significant burden and cost to the individuals living with these conditions and to society (10)(11)(12). It is critical to find ways to help individuals with musculoskeletal conditions to remain employed, especially as the potential burden of these conditions is expected to increase with the aging of the population in many industrialized nations (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ankylosing spondylitis (AS) are subject to adverse work outcomes, including work disability, sick leave, and presenteeism (i.e., reduced productivity while at work) (1,2). In the prebiologic agent era, the increased risks of work disability in patients with AS compared to the general population were 3.1 and 2.7 times in The Netherlands (n 5 658) and US (n 5 549), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with AS are also subject to a markedly higher risk and length of sick leave compared to the general popula-tion, according to a study in The Netherlands, France, and Belgium (n 5 113) (5,6). Presenteeism in AS patients has never been compared to the general population, but 53% of the patients (n 5 72) experienced limitations while at work and reported reduced efficiency due to AS (3.3 on a 0-10 scale) (2). The productivity loss at work in AS patients was estimated to be 8.3% (n 5 66) (7) and 18.9% (n 5 315) (8) using the 25-item and 16-item Work Limitations Questionnaires, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations in physical and social functioning lead to employment and household work disability and this causes increase in healthcare and non-healthcare expenditure and loss of income (8)(9)(10). In a previous study, the average annual healthcare and non-healthcare expenditure was found to be €431 per patient and the average loss of annual income was found to be €1371 per patient in Netherlands, France, and Belgium (8).…”
Section: Introductionmentioning
confidence: 99%
“…The cross-cultural adaptation was a practical way of adapting an instrument to another language and basically the initial step before validation studies. The health and labour questionnaire (HLQ) was relatively frequently used instrument in especially rheumatic disease research studies, although it was a non-disease-specific general questionnaire (9,11,16,17). The HLQ has some advantages that it is suitable for self-assessment and furthermore, the modular structure of the questionnaire enables the omission of questions, which are not applicable to the study population (17).…”
Section: Introductionmentioning
confidence: 99%